The impact of the method of consent on response rates in the ISAAC time trends study. - Ellwood, P (2010)
BACKGROUND: Centres in Phases I and III of the International Study of Asthma and Allergies in Childhood (ISAAC) programme used the method of consent (passive or active) required by local ethics committees. METHODS: Retrospectively, relationships between achieved response rates and method of consent for 13-14 and 6-7-year-olds (adolescents and children, respectively), were examined between phases and between English and non-English language centres. RESULTS: Information was obtained for 113 of 115 centres for adolescents and 72/72 centres for children. Both age groups: most centres using passive consent achieved high response rates (>80% adolescents and >70% children). English language centres using active consent showed a larger decrease in response rate. Adolescents: seven centres changed from passive consent in Phase I to active consent in Phase III (median decrease of 13%), with five centres showing lower response rates (as low as 34%). Children: no centre changed consent method between phases. Centres using active consent had lower median response rates (lowest response rate 45%). CONCLUSION: The requirement for active consent for population school-based questionnaire studies can impact negatively on response rates, particularly English language centres, thus adversely affecting the validity of the data. Ethics committees need to consider this issue carefully.